2020
DOI: 10.1136/bmjqs-2019-009704
|View full text |Cite
|
Sign up to set email alerts
|

Learning from complaints in healthcare: a realist review of academic literature, policy evidence and front-line insights

Abstract: IntroductionA global rise in patient complaints has been accompanied by growing research to effectively analyse complaints for safer, more patient-centric care. Most patients and families complain to improve the quality of healthcare, yet progress has been complicated by a system primarily designed for case-by-case complaint handling.AimTo understand how to effectively integrate patient-centric complaint handling with quality monitoring and improvement.MethodLiterature screening and patient codesign shaped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 100 publications
(248 reference statements)
2
45
0
1
Order By: Relevance
“… 8 43 56 Furthermore, a receptive and learning institutional culture can help staff recognise the value of transparent and fair feedback management. 43 57 Consistent with our results, scholars have found that transparency in feedback management can enhance the health system’s credibility and foster patient trust, 58 thus contributing to bridging the information asymmetry and alleviating potential losses of agency. This confirms our initial CMO which linked clear guidelines and processes along with support to facility staff, with a sense of being respected and motivation to value and act on feedback.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“… 8 43 56 Furthermore, a receptive and learning institutional culture can help staff recognise the value of transparent and fair feedback management. 43 57 Consistent with our results, scholars have found that transparency in feedback management can enhance the health system’s credibility and foster patient trust, 58 thus contributing to bridging the information asymmetry and alleviating potential losses of agency. This confirms our initial CMO which linked clear guidelines and processes along with support to facility staff, with a sense of being respected and motivation to value and act on feedback.…”
Section: Resultssupporting
confidence: 88%
“…[38][39][40][41][42] Our findings highlight that while being aware is necessary, mere awareness is not enough for exercising agency and rights, echoing the literature on limited feedback by the socioeconomically disadvantaged in Nepal, Russia and Israel 11 41 42 and highincome contexts such as the UK. 43 Fears of retribution and distrust of the system consistently underpin people's decisions not to complain. 11 41 42 44-46 Patients distrust feedback systems because they doubt the benevolence of the health system and are afraid of retribution, which undermines their agency as the likely principals when providing feedback.…”
Section: Collecting Feedbackmentioning
confidence: 99%
“…There are various groups who could use and benefit from our dental complaint taxonomy, including DRAs, professional associations, educators, researchers, patients and the public. First, DRAs could use the taxonomy to monitor the type and frequency of complaints made by the public over time or across jurisdictions [22]; in other words, findings could be used for quality assurance and improvement activities. Second, as our taxonomy was developed through complaints made by the public, educators, associations and regulators could use the taxonomy and our findings to identify topics relevant for undergraduate and graduate dental education and for continuing dental education opportunities for dental professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Examination and diagnosis Incomplete or improper patient examination [1][2][3][4] Diagnostic errors, including missed diagnosis and misdiagnosis [2][3][4][5][6][7][8][9][10][11] Failing or refusing to refer the patient to another dental professional 1,2,10,[12][13][14] Treatment Performing an inappropriate, unnecessary or inadequate procedure 2, 6-8, 12, 13, 15-17 Failed, delayed or incomplete treatment 9,12,14,18 Procedural errors, including performing the procedure on the incorrect tooth or site, inhaling or swallowing an object, choking or brief respiratory arrest, file fractures, improper filling, adverse reaction to latex or materials, soft tissue burns from heated instruments, and perforation; 1, 3, 4,7-9, 11-13, 19-22, 24 Adverse drug or anaesthesia reaction 5,12,22,25 including overdose 1,8,20 Treatment complications or iatrogenic injuries, including infections, soft tissue injuries, persistent bleeding, injuries to adjacent tooth, nerve damage or injury, eye damage, and damaged, broken, or tooth loss; 4,7,8,9,11,12,19,20,21,26 Unmet treatment expect...…”
Section: Complaint Issuementioning
confidence: 99%
See 1 more Smart Citation